The Role Of A Creative Director In Increasing Brand Awareness Through Commercial Video Advertising For Chicago Fried Chicken - Al Ghofiqi, Muhammad Rizieq; Melano, Fiqie Lavani (eProceedings of Management, 2025)
This research investigates the role of a Creative Director in increasing brand awareness through the development of acommercial video advertisement for Chicago Fried Chicken. The study aims to address the challenges faced by localbrands in the highly competitive food and beverage (F&B) industry. Using an innovative storytelling approach, theresearch integrates visual elements, narrative techniques, and communication strategies to evoke emotional impactand improve audience engagement. The advertisement was tailored for digital platforms, particularly YouTube, totarget lower-middle-class consumers, emphasizing product advantages to enhance recognition and attract newcustomers. The findings highlight the critical role of a Creative Director in conceptualizing and delivering compellingbrand storytelling to communicate effectively with the audience and achieve the desired marketing objectives.Keywords: Creative Director, Brand Awareness, Commercial Video, Storytelling, Chicago Fried Chicken.